Entry-Level Spatial and General Non-verbal Reasoning: Can These Abilities be Used as a Predictor for Anatomy Performance in Veterinary Medical Students? - Gutierrez, Juan Claudio; Holladay, Steven D.; Arzi, Boaz; Gomez, Marcelo; Pollard, Rachel; Youngblood, Patricia; Srivastava, Sakti (Frontiers in Veterinary Science, 2018)
There is currently limited available information, but growing interest, in possible relationships between spatial visualization skills in medical students and their academic performance in select areas of the curriculum such as radiographic interpretation and anatomy. There is very limited comparable information on how entry-level spatial visualization skills may correlate with macroscopic anatomy performance in veterinary medical students exposed to an integrated curriculum. The present study made use of a battery of two short tests that measure spatial ability: Guay’s visualization of views test (VVT) and mental rotation test (MRT) and, one test that measures general non-verbal reasoning abilities: Raven’s Advanced Progressive Matrices Test, short form (APMT). Tests were given to 1st-year veterinary medical students (n=124) immediately before commencing the integrated veterinary medical curriculum. Results show there is a positive correlation between entry-level spatial ability and non verbal general reasoning scores confirming these abilities are linked (r: +0.22 and + 0.3 for VVT/APMT and MRT/APMT respectively). The dispersion and inconsistency of significant positive correlation between anatomy practical exams grade and spatial and general reasoning scores suggest these abilities either do not correlate with anatomy practical exams grade or, are overcome with progression through the anatomy courses. Males scored higher than females in the spatial ability tests: 16.59 vs. 12.06 for VVT (p = 0.01) and 19.0 vs. 14.68 for MRT (p = 0.01). Scores for APMT did not show a significant difference by gender.